Application of information technology in university education - Nguyễn Thị Thanh Thảo (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Technology Information (IT) is one of the most wonderful inventions of humankind. IT has made a huge contribution in comprehensive development of the world. IT is also an “effective assistant” for all plans of that development. The education, like other fields such as technology, the faster it will progress to success. The more modern people are, the modern society is, the more new the world is, so the way of the education also needs to be quick and pervasive. Especially, in the current educational circumstance, IT shows its important role more than ever.